EFFECT OF BETA-BLOCKERS AND STUDY OF AGGREGATiVE ACTIVITY OF THROMBOCYTES IN PATiENTS WITH DILATED CARDIOMYOPATHY - P. N. Isakhanova; Yu. N. Ziyaev (Acta Biomedica Scientifica, 2012)
The aim. was to study peculiarities of ischemic and idiopathic dilated cardiomyopathy and. aggregative activity of thrombocytes and. also the response to the therapy by beta-blockers (Atenolol and Bisoprolol). Material and. methods: study of aggregative activity of thrombocytes in patients with ischemic and. idiopathic dilated cardiomyopathy, study of dynamics of aggregative activity of thrombocytes in patients with ischemic and. idiopathic dilated cardiomyopathy under the influence of 3-months therapy by Atenolol and. Bisoprolol. Research of aggregative activity of thrombocytes in patients involved in the research demonstrated reliable increase of speed and. maximum amplitude of thrombocytes aggregation at addition of 0,5 normal solution of ADP and. reliabie decrease of time of reaching of maximum amplitude of aggregation. Comparison of patients with idiopathic and. ischemic dilated cardiomyopathy revealed reliable increase of all the indices of aggregative activity in patients with ischemic dilated cardiomyopathy in comparison with ones with idiopathic form in both groups of therapy. The research shows that patients with dilated cardiomyopathy have an activation of aggregative activity of thrombocytes that is more evident in patients with ischemic form. Prolonged use of Bisoprolol allows to achieve more evident antiaggregative effect of used base therapy in comparison with use of Atenolol.